SOCIAL STUDIES LEARNING FOR THE DEVELOPMENT OF EMPATHIC AWARENESS - Wiyanarti, Erlina (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
The background of this research is the tendency of emphatic awareness learning that is being overlooked in the social studies in schools. The main problem addressed in this research is the social studies learning for the development of emphatic awareness of student of elementary school level in Bandung.The objectives of this research are (1) to design a model of social studies learning program for the development of emphatic awareness of fifth-grade students of elementary school in Bandung, (2) to test the effectiveness of the learning program, and (3) to identify difficulties encountered by elementary school teachers in developing social studies learning for the development of emphatic awareness of fifth-grade students. The methodology of this research is using multi method approach with two-phase designs model or double research strategy. After the research is conducted, based on analysis and discussion of the phase 1 result of limited testing, a stable emphatic awareness learning model was found, then focusing revision in cycle. The early model in product testing was conducted by using pair t-sampling. The result shows that social studies learning model using story telling method is effective in developing emphatic awareness of student in all indicators. The difficulties faced by teachers are more related to the level of understanding of emphatic awareness, creativity, and innovation level which are not optimum. Based on the analysis and discussion and the result of the research, the general conclusion is the development study have met the objective. Emphatic awareness learning model can be applied through planing management and implementation of learning through storytelling method which have high applicability rating with a favorable result and has good implication theoretically and practically. The proposed recommendations are beneficial for model application and for further studies.